If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 = -35 + -5x Reorder the terms: 10 + 2x = -35 + -5x Solving 10 + 2x = -35 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 10 + 2x + 5x = -35 + -5x + 5x Combine like terms: 2x + 5x = 7x 10 + 7x = -35 + -5x + 5x Combine like terms: -5x + 5x = 0 10 + 7x = -35 + 0 10 + 7x = -35 Add '-10' to each side of the equation. 10 + -10 + 7x = -35 + -10 Combine like terms: 10 + -10 = 0 0 + 7x = -35 + -10 7x = -35 + -10 Combine like terms: -35 + -10 = -45 7x = -45 Divide each side by '7'. x = -6.428571429 Simplifying x = -6.428571429
| 3x-5=2/5 | | (20-2z)/3=0 | | -5-2[2x-4(x+7)]-6= | | x-2=15x-74 | | 2(5+3x)=1 | | 5x+3+-x=2x+1+2x+3 | | 6x-2=15x-72 | | 5X-4-6X=-3+3 | | 3x+1x+1+1x+2=39 | | 12x+34x=10x+200 | | 4X-2-3X=1-8 | | 3X+4X+4=53 | | y-14=-7 | | 3(x-1)=2(x+5) | | -13+x=-8 | | 4X+12X-35X=-9+47 | | 24=c-16 | | 2x-(1008/x)=6 | | 12/-4z=-8 | | 11x-1=2x+9 | | 18=t-5 | | 9+8(8-2)3= | | Px^2-(p-q)x-q=0 | | (((3*(x^3)-5*x))^100)/ln(x) | | 9k^2+12k+1=0 | | 7(x+5)-10=7x+20-5 | | 172x+160=20x | | 4(y-1)-2=3y | | 4y-4/15 | | 3-7x=3x-2 | | 6(2l+3)=54 | | 4-2x-1=11-4x |